Supply Chain Management for Bioenergy and Bioresources - Bochtis, Dionysis; Achillas, Charisios (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In the modern world, the competitiveness of bioenergy- and/or bioresources-related activities heavily depends on the effectiveness of supply chain management. A large number of multidisciplinary topics are involved in the bioresources and bioenergy production fields. Although the technical issues that are related with the topic are well-discussed and do not represent major barriers, supply chain management issues, such as design of the network, collection, storage or transportation of bioresources, are still considered as fundamental questions that need to be answered to enable the optimal exploitation of bioenergy and bioresources. Moreover, modeling of material and energy flows; identification of the dynamic character of the supply chains; available reverse logistics (waste management) alternatives; economic, social and environmental sustainability of bioresource supply chains; novelty in the applied business models; and decision support frameworks towards efficient supply chain management for bioenergy and bioresources present critical operational sustainability issues and business-making potential. This Special Issue, entitled "Supply Chain Management for Bioenergy and Bioresources", seeks to contribute to the bioenergy and bioresources agenda through enhanced scientific and multi-disciplinary knowledge that may boost the performance efficiency of supply chain management and support the decision-making process of stakeholders. To that end, the Special Issue includes one extensive review on yellow and woody biomass supply-chain management, together with six original papers which span a number of innovative, multifaceted, technical developments that are related to all different echelons of supply chain management for bioenergy and bioresources.